Meningkatkan Kemandirian Siswa Selama Pembelajaran Daring Melalui Model Pembelajaran Virtual Pada Siswa Kelas 2 SD N Grabag 1 Kabupaten Magelang - Mayang, Sekar (Prosiding University Research Colloquium, 2021)
The purpose of this research is to increase student independence during online learning through a virtual learning model in 2nd grade students of N Grabag 1 Magelang Elementary School. This study uses Class Action Research (PTK). Total of 5 students were selected in this study using interview techniques, questionnaires, and pasttests. Data collection techniques in the form of questionnaires and student learning outcomes. Pasttest given to find out student conclusions during online learning with virtual model. Results in cycle I students are still less independent in learning for cycle II there is an increase in student learning independence. Thus, with the online virtual learning model in 2nd grade students can be applied